Conducting Qualitative Research on Children and Adolescents With Life-Limiting Conditions: Are We Really Listening? - Oetting-Roß, Claudia; Ullrich, Charlotte; Schnepp, Wilfried; Büscher, Andreas (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2016)
In this article, we discuss how to incorporate the perspectives of children and adolescents with life-limiting conditions into qualitative research studies by actively involving these children; e.g., via qualitative interviews. First, an overview of living conditions and homecare of these children and adolescents is given. Next, results from empirical studies are discussed with respect to challenges connected to the active participation of these children and adolescents and their families in qualitative research. This discussion is then summarized with a focus on the central threads. Against this background, strategies for a sensitive integration of life-limiting children and adolescents into qualitative research are derived. The thesis of this article is informed by an ongoing qualitative study with children and adolescents with life-limiting conditions that focus on their perceptions and points of view. We offer suggestions for planning, conducting, and evaluating research projects with children and adolescents not only with life-limiting conditions. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs1602241